Intact Organization of Tactile Space Perception in Isolated Focal Dystonia. Issue 8 (4th May 2021) - Mainka, Tina; Azañón, Elena; Zeuner, Kirsten E.; Knutzen, Arne; Bäumer, Tobias; Neumann, Wolf‐Julian; Borngräber, Friederike; Kühn, Andrea A.; Longo, Matthew R.; Ganos, Christos
ABSTRACT: Background: Systematic perceptual distortions of tactile space have been documented in healthy adults. In isolated focal dystonia impaired spatial somatosensory processing is suggested to be a central pathophysiological finding, but the structure of tactile space for different body parts has not been previously explored. Objectives: The objective of this study was to assess tactile space organization with a novel behavioral paradigm of tactile distance perception in patients with isolated focal dystonia and controls. Methods: Three groups of isolated focal dystonia patients (cervical dystonia, blepharospasm/Meige syndrome, focal hand dystonia) and controls estimated perceived distances between 2 touches across 8 orientations on the back of both hands and the forehead. Results: Stimulus size judgments differed significantly across orientations in all groups replicating distortions of tactile space known for healthy individuals. There were no differences between groups in the behavioral parameters we assessed on the hands and forehead. Conclusions: Tactile space organization is comparable between patients with isolated focal dystonia and healthy controls in dystonic and unaffected body parts. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society